CP-109 Evaluation of clinical, economic and organisational impacts of pharmacists' interventions on immunosuppressive therapy management among lung transplant outpatients. (25th February 2017) - Duwez, M; Chanoine, S; Lepelley, M; Vo, TH; Mazet, R; Allenet, B; Camara, B; Bedouch, P
Abstract : Background: Lung transplant recipients require multidisciplinary care because of the complexity of therapeutic management. Clinical pharmacists are able to detect drug related problems (DRPs) and provide recommendations to physicians. The potential significance of pharmacists' interventions (PIs) has never been studied by a multidimensional approach in lung transplantation (LT). Purpose: We aimed to assess the clinical, economic and organisational impact of PIs on immunosuppressive management among lung transplant outpatients. Material and methods: In our centre, PIs are comprehensively and prospectively collected on Act-IP database, a free access website observatory created by the French Society of Clinical Pharmacy (SFPC) from 2009 onward. Each PI includes patient features, a description of the DRP and the PI according to the SFPC classification. A retrospective analysis of the PIs was performed from 1 January 2009 to 31 December 2015 by an expert committee including a clinical pharmacist, pharmacovigilant and pneumologist. The impact of accepted PIs was assessed according to the validated multidimensional 'CLEO' scale, which includes three dimensions: CLinical (harmful, null, minor, moderate, major, lethal, non-determined), Economic (cost increase, no change, cost decrease, not determined) and Organisational impacts (unfavourable, null, favourable, not determined). Results: Among the 1568 PIs performed over the 7 year period, 713 (45.5%) were related to immunosuppressive therapy for which the physician's acceptance rate was 94.0%. The expert committee considered the clinical impact of PIs as major, moderate and minor in 9.6%, 67.0% and 22.8%, respectively. Major clinical impact was mainly related to drug–drug interactions between immunosuppressants and antifungals (56.0%). Wrong dose was the main cause of moderate clinical impact (75.0%). While 41.6% of PIs led to a cost increase due to dose increase or adding of drug monitoring, 44.8% of PIs helped a cost decrease due to dose decrease or drug discontinuation (44.8%). Most PIs did not have an organisational impact for healthcare professionals (99.1%). Conclusion: This is the first study which has evaluated the clinical, economic and organisational impacts of PIs in lung transplant outpatients. Our findings show that clinical pharmacists play a key role in optimising immunosuppressive therapy management in LT. As experts in drug therapy, clinical pharmacists are able to detect and resolve DRPs to improve patient care. No conflict of interest